EFFECT OF CHEMICAL CONTROL ON THE SANITY OF FOREST SPECIES SEEDS - Silva, Lilianne Gomes da; Cosmi, Fernando Carrara; Jesus Junior, Waldir Cintra de; Souza, Antonio Fernando de; Moraes, Willian Bucker [UNESP] (Centro Pesquisas Florestais, Ufsm, 2011)
This study evaluated the effect of different fungicide and sodium hypochlorite treatments in reducing the incidence of fungi on seeds of native species of the Atlantic rainforest. The experiment was done using the completely randomized design in a 5x5 factorial with five levels of factor A (forest species) and five levels of factor B (chemical treatment and surface disinfection with sodium hypochlorite) with four replications. The fungal genera Fusarium, Alternaria, Aspergillus and Penicillium were identified. The species 'Jacarandada- Bahia' and 'Ipe-roxo' had lower fungal incidence, 1.0% and 1.3%, respectively. Except for 'Angico Vermelho', the fungicide pencycurom and sodium hypochlorite were not significantly different from the control in the species evaluated. Seed treatment with fungicides 'Captan' and 'Tiram' yielded satisfactory results in reducing the incidence of fungal contamination in forest species seeds.
Keywords: fungicide treatment; sodium hypochlorite; seed pathology